2008
DOI: 10.1197/jamia.m2602
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Electronic Clinical Reminders to Improve Medication Laboratory Monitoring

Abstract: We identified high rates of appropriate laboratory monitoring, and electronic reminders did not significantly improve these monitoring rates. Future studies should focus on settings with lower baseline adherence rates and alternate drug-laboratory combinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 38 publications
0
48
0
Order By: Relevance
“…Positive effects were also found by Feldstein et al 20 evaluating the effect of CCDSSs reminding physicians of 10 possible drug-laboratory interactions in Kaiser Permanente primary care practices. That this trend is not absolute is illustrated by the study by Matheny et al 30 studying a similar CCDSS aimed at 14 drug-laboratory interactions within the Longitudinal Medical Record at Brigham & Women's Hospital. They could not report a significant effect on appropriateness of testing, but an important note to be made is that the baseline rates of overdue testing were already very low before the implementation of the CCDSS, hence leaving very little margin for improvement.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Positive effects were also found by Feldstein et al 20 evaluating the effect of CCDSSs reminding physicians of 10 possible drug-laboratory interactions in Kaiser Permanente primary care practices. That this trend is not absolute is illustrated by the study by Matheny et al 30 studying a similar CCDSS aimed at 14 drug-laboratory interactions within the Longitudinal Medical Record at Brigham & Women's Hospital. They could not report a significant effect on appropriateness of testing, but an important note to be made is that the baseline rates of overdue testing were already very low before the implementation of the CCDSS, hence leaving very little margin for improvement.…”
Section: Discussionmentioning
confidence: 92%
“…[20][21][22][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Eight studies (35%) were conducted in Europe. 23,[38][39][40][41][42][43][44][45] One study (4%) was conducted in Europe and Australia.…”
Section: Included Studiesmentioning
confidence: 99%
“…While prior literature either evaluates only physician test ordering 5,6 or overall test completion, 8,9 rarely are both reported. 20,40 Most studies have reported only completion rates, usually determined from claims data, 41 while we have separated outcomes into test ordering and patient completion of ordered tests.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report clinician ordering only, 5,6 while others report overall test completion rates. [7][8][9][10][11] In addition, little information is available about why patients fail to complete ordered laboratory tests. Patient understanding of the reason for testing may affect test adherence, as suggested by one study of warfarin.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies of the impact of EHRs on quality have shown inconsistent results 312. No randomized clinical trial or longitudinal study using a direct measure of clinical quality has been conducted to test this assumption.…”
Section: Introductionmentioning
confidence: 99%